Government Authority in Regulating Employment Relations between Employers and Workers/Laborers in Indonesia - Rika Jamin Marbun; Abdurrahman Harits Ketaren; Siti Nurhayati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The working relationship between employers and workers/labourers is civil/private in nature because it was born after the existence of a work agreement. The existence of jobs, orders and wages as elements of work relations is left to the parties. The work agreement as the basis of the employment relationship is an autonomous rule for employers and workers/laborers in exercising their rights and obligations. However, work agreements do not fully contain private elements. The position of the worker/laborer and the entrepreneur is not balanced, for example in terms of "work" and "orders" the worker/laborer is in a weak position because the employer has previously determined it according to the type of work agreed upon. Likewise the issue of "wages", even though the entrepreneur has set the amount, it may not conflict with the provisions of labor regulations. Labor is very crucial because it is one of the main pillars in carrying out national development. Therefore, a heteronomous rule is needed as a safeguard in supervising the working relationship between the parties. This raises the public aspect in the field of employment. This research will discuss the authority of the government in employment relations. The research method uses normative juridical with a focus on laws and regulations. The presence of the government is principally in order to monitor and balance the relationship between the two parties through labor law instruments that apply as heteronomous rules. This raises the public aspect in the field of employment. This research will discuss the authority of the government in employment relations. The research method uses normative juridical with a focus on laws and regulations. The presence of the government is principally in order to monitor and balance the relationship between the two parties through labor law instruments that apply as heteronomous rules. This raises the public aspect in the field of employment. This research will discuss the authority of the government in employment relations. The research method uses normative juridical with a focus on laws and regulations. The presence of the government is principally in order to monitor and balance the relationship between the two parties through labor law instruments that apply as heteronomous rules.